Группалар жəне оларды оқып-үйренудің əдістемелік аспектілері - Жетпісов, Қ.; Базылжанова, А.С.; Жилкибаева, Л.К. (Қарму басп., 2011)
В современной алгебре изучение понятия гомоморфизма и методология построения фактор-алгебр основываются на понятии «конгруэнция». В данной статье показано применение базовых конструкций построения фактор-систем и технологий применения теоремы о гомоморфизмах, что демонстрируется на примерах групп. Кроме того, обобщая опыт апробированного изучения теории групп в высших учебных заведениях с позиции современной алгебры, авторы предлагают методику изучения концепций изоморфизма и гомоморфизма и формирования понятия «фактор-группа» на основе отношения конгруэнции. In the modern algebra the study of the notion of homomorphism and the methodology of factor algebras building are based on the notion «congruence». In the article a using of basic constructions of factor systems building and technologies of a using theorem about homomorphismes are given on examples of groups. In addition generalizing a experience of certified study of the group theory in the institutions of higher education from the position of modern algebra we suggest the method of the isomorphism and homomorphism conceptions studying and the «factor group» notion forming based on the congruence relation.
The groups and the methodical aspects of their study